AKAL DAN KECERDASANDALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Muhammad Isnaini; Iskandar (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2021)
The research study carried out was literature where the results of the research carried out contained several findings in the study, including; First, Humans were created by Allah SWT in a perfect form which makes it different from other creatures. Second, the human mind is a gift from Allah SWT, which is used to think, understand, be able to understand something, from within the human being himself, so that humans have the readiness to absorb everything. Third, religion is a matter of reason and its use must be in accordance with the provisions and limits that have been set and not result in absolute and absolute thinking that can harm humans themselves. Fourth, human intelligence is described through the ability of humans themselves to be able to restrain their lusts, those who do the most charity to remember death and the best in preparing provisions to face life after death. Fifth, in the context of human life today, the intelligence referred to includes intelligence IQ (Intellegence Quotient), EQ (Emotional Quotient), and SQ (Spiritual Quotient) and there are even other intelligences as part of one's potential that must always be honed and developed. Sixth, the function of reason which is accompanied by good intelligence in Islamic education, with the concepts of tadhakkur, tadabbur, tafakkur and has knowledge and faith, has a very important role in realizing quality Islamic education